Genetics of morphological characters in rice (Oryza sativa) - TOMAR, J B; PRASAD, S C; KUMARI, MADHU (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted at the NBPGR, Ranchi and rice research farm, BAU, Ranchi during 1989-94 usingsix cultivars; 'NIC 40484', 'NIC 10514', 'CR 3001', 'AC 1225', 'Blackgora' and 'Browngora' rice (Oryza sativa L.) wereused to study the inheritance and linkage relationship of some morphological traits. It was found that presence ofnormal ligule was dominant over ligule less, normal auricle over auricleless, normal junctura over rudimentary junctura,awning over awnless, unipistillate ovary over multi pistillate ovary, short glume over long glume and normal culm overbrittle culm in the 'CR 3001' x 'AC 1225' cross. The characters-ligule, auricle, junctura, glume, pistil number, awn and brittle culm were found to be governed by one pair of major genes. The pigmentation in F, was observed in leaf axiland apiculus but pigmentation in leaf blade and internode was dominant but inhibited. The pigmentation was found tobe governed by four dominant genes in leaf axil (162P:94G), 2 gene pairs in leaf blade and internode (3P: 13G).and 3major gene pairs in apiculus (45P: 19G) in 'CR 3001 'x 'AC 1225' cross. The sheathed panicle was found to be governedby single dominant gene (3S:1E) in 'NIC 40484' and inhibitory genes (13S:3E) in 'NlC 10514'. The gene for sheathed panicle in 'NIC 40484' was found to be located on chromosome 12. The red kernel in 'Browngora' was controlled by 3 dominant complementary genes. The linkage studies was carried out in 'CR 3001' x 'AC 1225' cross only. The genes lg, Pin, PI and Px were found to be linked. Based on crossover values, gene order on the linear scale was found to be Ig-Pin-Pl and Px in linkage group II.